"Uncle Wm. Bemister" - Rorke Family (1865)
William Bemister. William Bemister (1823-1902), son of William Willis Bemister and Ann (Howell) Bemister, was born at Carbonear in July 1823. He married Dorcas Charlotte Bartlett, daughter of Joseph Bartlett of Twillingate, at Grantham, Canada West, on 6 October 1856 and had three daughters. William was the brother of Capt. Willis Bemister, Hon. John G. Bemister, Mary (Bemister) Forward and Sarah Jane (Bemister) Pike. He was also an uncle of Ernest Edward Forward and great-uncle of Kathleen (Forward) Rorke. William died at Toronto on 30 May 1902. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.